Coordinated Halide and Pseudo Halide‐Dependent Structures and Photoluminescence of Defective Double Cubane Zinc(II) Clusters. Issue 12 (25th February 2021) - Kuramitsu, Toshiaki; Kusumoto, Sotaro; Ohmagari, Hitomi; Hasegawa, Miki; Thuéry, Pierre; Kim, Yang; Hayami, Shinya; Nakamura, Masaaki
Abstract: Tetranuclear zinc(II) complexes [Zn4 (L )4 (μ3 ‐OCH3 )2 (X)2 ] (L =2‐((benzyloxy)carbonyl)‐6‐methoxyphenolate; X=Cl − (1 ), Br − (2 ), I − (3 ), N3 − (4 ), or NCS − (5 )), have "defective" double‐cubane cores [Zn4 O6 ], which are bridged by two μ3 ‐methoxo and four μ2 ‐phenolato oxygen atoms in each discrete complex. In halide complexes 1, 2 and 3, two zinc(II) ions are in slightly distorted octahedral coordinations and the other two in geometries close to the severely distorted trigonal bipyramid, respectively, while all four zinc(II) in pseudo halide complexes 4 and 5 show slightly distorted octahedral geometries. The complexes exhibit blue fluorescence (λmax =415–428 nm) with high photoluminescence quantum yields (PLQYS, Φ em ) in the range of 0.22‐0.53 at room temperature in the solid state. Complex 5 has the highest Φ em among the alkoxo‐bridged multinuclear zinc(II) clusters ever reported. Abstract : Tetranuclear zinc(II) clusters of defective double cubane structures with monodentate anions and benzyl‐functionalized o ‐vanillic acid ligands exhibit blue fluorescence (λmax =415–428 nm) with high photoluminescence quantum yields (PLQYS, Φ em ) in the range of 0.22‐0.53.